Regulations on filiation and family in the definition of citizen rights between the end of the 19th century and the beginning of the 20th century (Argentina, Chile, Uruguay) - Paz Landeira Florencia; LLobet Valeria (Dialogos, 2019)
This paper presents an analytical review of the literature on the regional debates in Argentina, Chile and Uruguay on family, marriage and filiation raised around the drafting of civil codes in the last decades of the nineteenth century and its first reforms, during the first half of the twentieth century. It questions the different legal mechanisms - and the arguments on which they were based - through which the demarcations between the public and the private, the political and the intimate, the natural and the social were established and regulated.